2011
DOI: 10.1159/000323845
|View full text |Cite
|
Sign up to set email alerts
|

UVC Irradiation for Pathogen Reduction of Platelet Concentrates and Plasma

Abstract: Besides the current efforts devoted to microbial risk reduction, pathogen inactivation technologies promise reduction of the residual risk of known and emerging infectious agents. A novel pathogen reduction process for platelets, the THERAFLEX UV-Platelets system, has been developed and is under clinical evaluation for its efficacy and safety. In addition, proof of principle has been shown for UVC treatment of plasma units. The pathogen reduction process is based on application of UVC light of a specific wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(159 citation statements)
references
References 54 publications
(61 reference statements)
9
147
0
3
Order By: Relevance
“…Dabei zeigte sich mit steigender UVC-Dosis eine Zunahme der Inaktivierungseffizienz [123]. Das THERAFLEX Verfahren ist gegenwärtig für TK in Additivlösung mit einer UV-Dosis von 0,2 J/cm² ausgelegt [121]. Diese Spezifikation wurde auch in der präklinischen Entwicklung des THERAFLEX UV-Platelets Verfahrens verwendet [124,125].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified
See 2 more Smart Citations
“…Dabei zeigte sich mit steigender UVC-Dosis eine Zunahme der Inaktivierungseffizienz [123]. Das THERAFLEX Verfahren ist gegenwärtig für TK in Additivlösung mit einer UV-Dosis von 0,2 J/cm² ausgelegt [121]. Diese Spezifikation wurde auch in der präklinischen Entwicklung des THERAFLEX UV-Platelets Verfahrens verwendet [124,125].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified
“…Enterobacter cloacae 6,3 ± 0,6 [134] Escherichia coli 7,3 ± 0,4 [127] Klebsiella pneumoniae 5,9 ± 0,7 [127] Morganella morganii 7,5 ± 0,3 [134] Proteus mirabilis 7,0 ± 0,6 [134] Pseudomonas aeruginosa ≥ 4,92 [121] Pseudomonas fluorescens 7,1 ± 0,4 [134] Serratia marcescens 5,8 ± 0,2 [134] Bakterien, gram-positiv…”
Section: Theraflex: Bakterien Tk Referenzenunclassified
See 1 more Smart Citation
“…Indeed, it has been estimated that residual quantities of S-59 (1 μg/kg) and its photoproducts (115 μg/kg) have been infused to the platelet recipient after pathogen reduction using Intercept technology [52]. Even though toxicological studies in animals [52,66] and clinical trials [67][68][69][70] have demonstrated the safety of photochemical-based pathogen reduction technologies, long-term studies may be needed for the evaluation of the risk of adverse effects, especially of carcinogenesis [23].…”
Section: Figmentioning
confidence: 99%
“…On the other hand, it has been difficult to assess the safety margin of psoralen or its photoproducts bound to or incorporated by platelets when transfused into a patient [23] and quantities infused into the recipient may be increased in the case of BM-hMSCs cultured for several passages in hPL prepared from pathogen-reduced PCs. Considering this and the fact that pathogen-reduced PCs using S-59 and UV-A are contraindicated in patients displaying allergy to psoralens, the use of hPL prepared from pathogen-reduced PCs using Intercept technology [36,71,72] for BM-hMSCs intended for clinical use may lead to a regulatory issue.…”
Section: Figmentioning
confidence: 99%